INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM POLA ASUH KELUARGA SASAK NUSA TENGGARA BARAT - Baiq Mulianah (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2019)
This study aims to describe the suitability of the Sasak family upbringing with Islamic education, the root of the shift and how to build a new upbringing that is compatible with Islam and the Sasak culture. Through a literature study with phenomenologicalstructural analysis, the writer found that there has indeed been a fundamental change in the parenting style of sasak family whose symptoms are easily seen in the behavior of children who are no longer naturally referring to Islamic values. The conclusions that researchers can draw from the research are: first, that the traditional parenting style of Sasak family is in accordance with Islamic education; secondly, that the shift in the upbringing of Sasak families that led to changes in behavior in present-day children is an accumulation of the collisions brought about by the current of globalization; and third, to build new patterns of Islamic values that are now mainstreamed such as the values of moderation and democracy can be a reference in building new parenting with the necessary adjustments in the realm of culture and tradition of Sasak.